Disease severity in familial cases of IBD. (1st March 2014) - Andreu, M.; Márquez, L.; Domènech, E.; Gisbert, J.P.; García, Garcia V.; Marín-Jiménez, Marin-Jimenez I.; Peñalva, Penalva M.; Gomollón, Gomollon F.; Calvet, X.; Merino, O.; Garcia-Planella, E.; Vázquez-Romero, Vazquez-Romero N.; et al.
Abstract: Background: Phenotypic traits of familial IBD relative to sporadic cases are controversial, probably related to limited statistical power of published evidence. Aim: To know if there are phenotype differences between familial and sporadic IBD, evaluating the prospective Spanish registry (ENEIDA) with 11, 983 cases. Methods: 5783 patients (48.3%) had ulcerative colitis (UC) and 6200 (51.7%) Crohn's disease (CD). Cases with one or more 1st, 2nd or 3rd degree relatives affected by UC/CD were defined as familial case. Results: In UC and CD, familial cases compared with sporadic cases had an earlier disease onset (UC: 33 years [IQR 25–44] vs 37 years [IQR 27–49]; p < 0.0001); (CD: 27 years [IQR 21–35] vs 29 years [IQR 22–40]; p < 0.0001), higher prevalence of extraintestinal immune-related manifestations (EIMs) (UC: 17.2% vs 14%; p = 0.04); (CD: 30.1% vs 23.6%; p < 0.0001). Familial CD had higher percentage of ileocolic location (42.7% vs 51.8%; p = 0.0001), penetrating behavior (21% vs 17.6%; p = 0.01) and perianal disease (32% vs 27.1%; p = 0.003). Differences are not influenced by degree of consanguinity. Conclusion: When a sufficiently powered cohort is evaluated, familial aggregation in IBD is associated to an earlier disease onset, more EIMs and more severe phenotype in CD. This feature should be taken into account at establishing predictors of disease course.